Efficacy of anakinra treatment in pediatric rheumatic diseases: Our single-center experience - Ferhat Demir; Eda Gürler; Betül Sözeri (Archives of Rheumatology, 2022)
Objectives: This study aims to present our experience on anakinra, a recombinant interleukin-1 (IL-1) receptor antagonist, and efficacy results in pediatric rheumatic diseases in our clinic. Patients and methods: Between July 1st, 2016 and July 1st, 2020, a total of 33 pediatric patients (18 males, 15 females; mean age: 6±3.4 years; range 4 to 13 years) with pediatric rheumatic diseases who were treated with anakinra were retrospectively analyzed. The patients with over one-month treatment period and followed for at least one year were included. Demographic and clinical findings, outcomes, adverse events, prior and/or additional treatments were collected at baseline, at 3 and 12 months of therapy. Results: There were 33 patients with different pediatric rheumatic diseases (11 with systemic juvenile idiopathic arthritis [sJIA] complicated by macrophage activation syndrome [MAS], six with hyperimmunoglobulin-D syndrome, five with cryopyrin-associated periodic syndrome, five with familial Mediterranean fever, four with idiopathic recurrent pericarditis, one with NLRP12-associated periodic fever syndrome and one with unclassified systemic autoinflammatory disease), in the study group. The complete response was observed 69.7% of patients, partial response in 24.2%, and no response in 6.1% at three months of treatment. Inactive disease status was achieved in 45.5% of the patients with remission-on medication and 18.2% of the patients with remission-off medication at the end of a year. Anakinra was switched to other biological treatments in 51.5% of patients (n=17). Biological switch to canakinumab and tocilizumab were observed in 70.6% and 29.4% of these patients. Except for local reactions (n=2), no adverse events were observed in any of the patients. Conclusion: Anakinra appears to be a promising treatment alternative owing to its rapid effect as a result of its short half-life in autoinflammatory conditions. While short-term therapy seems to be sufficient for the sJIA complicated by MAS, the patients with systemic autoinflammatory diseases maintenance a more anakinra-dependent course.